Semileptonic decays B-->pi lepton neutrino and D-->pi lepton neutrion from lattice QCD - RYAN, SINEAD MARIE (American Physical Society, 2001)
We present a lattice QCD calculation of the form factors and differential decay rates for semileptonic decays of the heavy-light mesons B and D to the final state pln . The results are obtained with three methodological improvements over previous lattice calculations: a matching procedure that reduces heavy-quark lattice artifacts, the first study of lattice-spacing dependence, and the introduction of kinematic cuts to reduce model dependence. We show that the main systematics are controllable ~within the quenched approximation! and outline how the calculations could be improved to aid current experiments in the determination of uVubu and uVcdu.
PUBLISHED
Keywords: Pure & Applied Mathematics